A PRAGMATIC APPROACH IN TEACHING HISTORY AND NATURAL SCIENCES TEACHERS TO FORMULATE EDUCATIONAL TASKS - Rzambetova Genjegul Aygaliyevna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
the article discusses methods, and approaches to the development of skills in the formation of educational tasks, through history lessons, which form students who are able to think independently, work independently with information, compare information, distinguish between them the necessary ideas, the most important in historical science, highlight the necessary information and topics for the student, as well as create useful educational tasks with pragmatic content.